Predictive Effect of Triglyceride Glucose−Related Parameters, Obesity Indices, and Lipid Ratios for Diabetes in a Chinese Population: A Prospective Cohort Study - Li, Xiaotong; Sun, Mengzi; Yang, Yixue; Yao, Nan; Yan, Shoumeng; Wang, Ling; Hu, Wenyu; Guo, Ruirui; Wang, Yuxiang; Li, Bo (Frontiers in Endocrinology, 2022)
Objective: The purpose of this study was to evaluate the association between Triglyceride glucose (TyG) index and new-onset diabetes under different glycemic states, and to compare the predictive value of TyG‑related parameters, obesity indices, and lipid ratios for new-onset diabetes. Methods: Data were collected from the China Health and Retirement Longitudinal Study (CHARLS), consisting of 6258 participants aged≥45 years. Participants were grouped according to their glycemic states. Cox proportional hazards models and restricted cubic spline regression were used to explore the association between TyG index and diabetes. Cox proportional hazard models were applied to confirm the predictive value of the optimal marker. Receiver operating characteristic (ROC) curves were used to compare the predictive value. Results: TyG index was positively correlated with the risk of diabetes (hazard ratio [HR], 1.75; 95% confidence interval [CI], 1.56-1.97), and the linear association was existed (p<0.001). The highest correlation with diabetes was visceral adiposity index (VAI) (HR, 2.04; 95%CI, 1.44-2.90) in normal fasting glucose (NFG) group and TyG-body mass index (TyG-BMI) (HR, 2.53; 95%CI, 1.97-3.26) in impaired fasting glucose (IFG) group. The largest area under curve (AUC) was observed in TyG-waist-to-height ratio (TyG-WHtR) in NFG group (AUC, 0.613; 95%CI,0.527-0.700), and TyG-BMI had the highest AUC in IFG group (AUC,0.643; 95%CI,0.601-0.685). Conclusion: The association between TyG index and new-onset diabetes was positive and linear. TyG-WHtR was a clinically effective marker for identifying the risks of diabetes in NFG group and TyG-BMI was an effective marker to predict diabetes in IFG group.